2019
DOI: 10.1021/acs.inorgchem.9b02836
|View full text |Cite
|
Sign up to set email alerts
|

Photo- and Thermoswitchable Half-Sandwich Nickel(II) Complex: [Ni(η5-C5H5)(IMes)(η1-NO2)]

Abstract: A new photoswitchable half-sandwich nitro Ni II complex with the N-heterocyclic carbene ligand was synthesized and successfully crystallized. The compound constitutes an analogue of a known nitrate nickel(II) compound, [Ni(η 5 -Cp)(IMes)(NO 3 )] (Cp = cyclopentadienyl, C 5 H 5 ; IMes = 1,3-bis(2,4,6trimethylphenyl)imidazol-2-ylidene), and crystallizes with two symmetry-independent molecules in the asymmetric unit. When irradiated with 470 nm lightemitting diode light, the complex molecules undergo a photoisome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 73 publications
6
36
1
Order By: Relevance
“…In the case of the QM/MM results, the energetic differences between the isomers are more emphasized (+18.0 and +31.2 kJ mol À1 , for the endoand exo-nitrito forms, respectively) than for the isolated molecule. A similar conclusion was drawn in our previous study (Kutniewska et al, 2019), but there the crystal confining effect was less pronounced. In addition, the above analysis confirms the validity of our refined structural model of all existing ground and metastable states.…”
Section: Computational Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…In the case of the QM/MM results, the energetic differences between the isomers are more emphasized (+18.0 and +31.2 kJ mol À1 , for the endoand exo-nitrito forms, respectively) than for the isolated molecule. A similar conclusion was drawn in our previous study (Kutniewska et al, 2019), but there the crystal confining effect was less pronounced. In addition, the above analysis confirms the validity of our refined structural model of all existing ground and metastable states.…”
Section: Computational Analysissupporting
confidence: 91%
“…However, note the above conclusions must be treated rather qualitatively. The estimated reaction cavity volume standard deviation amounted to about 0.5 Å 3 (Kutniewska et al, 2019), and the reported changes are within this range.…”
Section: In Situ Photocrystallographymentioning
confidence: 53%
See 3 more Smart Citations